2020
DOI: 10.3390/rs12111830
|View full text |Cite
|
Sign up to set email alerts
|

A Cloud-Based Evaluation of the National Land Cover Database to Support New Mexico’s Food–Energy–Water Systems

Abstract: Accurate estimation of land use/land cover (LULC) areas is critical, especially over the semi-arid environments of the southwestern United States where water shortage and loss of rangelands and croplands are affecting the food production systems. This study was conducted within the context of providing an improved understanding of New Mexico’s (NM’s) Food–Energy–Water Systems (FEWS) at the county level. The main goal of this analysis was to evaluate the most important LULC classes for NM’s FEWS by implementing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…However, during winter, summer, drought, and periods with extreme heat events, rangelands productivity decreases leading to increased demand for forage supplements to limit nutritional deficiency of grazing animals (Holechek et al, 2010;Samuelson et al, 2016). A recent study suggested that there have also been some land use land cover changes over some regions in New Mexico that can negatively affected the availability of suitable grazing rangelands that have been attributed mostly to woody plant encroachment (Gedefaw et al, 2020). These feed supplements are mostly based on irrigated and dryland production consisting mainly of combination of hay, grain sorghum, and corn (Schake et al, 1976;Davis et al, 1977;Holechek et al, 1989;Zaied et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, during winter, summer, drought, and periods with extreme heat events, rangelands productivity decreases leading to increased demand for forage supplements to limit nutritional deficiency of grazing animals (Holechek et al, 2010;Samuelson et al, 2016). A recent study suggested that there have also been some land use land cover changes over some regions in New Mexico that can negatively affected the availability of suitable grazing rangelands that have been attributed mostly to woody plant encroachment (Gedefaw et al, 2020). These feed supplements are mostly based on irrigated and dryland production consisting mainly of combination of hay, grain sorghum, and corn (Schake et al, 1976;Davis et al, 1977;Holechek et al, 1989;Zaied et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…New Mexico is specifically included in 11 of the Billion Dollar drought designations since 2000, and the threeyear 2011-13 period that severely affected New Mexico had an estimated $59.6 billion of losses nationally from the direct and indirect impacts that occurred (NOAA NCEI, 2020). For New Mexico, drought impacts affect crop and livestock productivity (Sawalhah et al, 2019;Zaied et al, 2019Zaied et al, , 2020Gedefaw et al, 2020); water supplies for public and ecosystem consumption; human, animal, and wildlife health; forests and wildfires; and recreation and tourism. These sectors have also become more vulnerable to natural hazards (i.e., droughts and wildfires) given changes occurring in the climate (NMOSE and NMWRRI, 2018).…”
Section: Drought and Food-energy-water Systems Of New Mexico Usamentioning
confidence: 99%
“…There were relatively higher human activities in northeastern, northwestern and southeastern NM represented by crude oil and natural gas production and livestock grazing practices. The prevalence of irreversible degradation and initiation of degradation were apparent in these regions [63]. On the other hand, significant changes in productivity (i.e., increase) was observed mostly in southwestern and northwestern NM, where forest were minimally influenced by human activities.…”
Section: Characteristics Of Changementioning
confidence: 92%
“…The area of world rangeland ecosystems ( Figure 1) is being impacted by several opposing anthropogenic and natural processes that can result in (a) an increase in rangeland areas such as conversions of tropical forests into grazing lands, glaciated areas into rangeland, and cropland to rangeland due to climate change, soil degradation, and/or depletion of irrigation water supply from aquifers and drying of rivers [15]; or conversely (b) a decrease in rangeland areas such as conversion of arable rangelands into croplands, and rangelands into urban landscapes (e.g., [14]). For example, recent findings suggest that the depletion of large aquifers used for irrigation, such as the Ogallala in the Southern Great Plains of the US, is already causing shifts from cropland to rangeland [21].…”
Section: Rangelands Energy and Climate Changementioning
confidence: 99%
“…Extreme weather events are already increasing in frequency and severity in the US and globally [5][6][7]. Global concern is growing over the possibility that eventual irreversible, catastrophic climate change will result in massive loss of human livelihoods and mortality through adverse impacts on food production systems over both croplands and rangelands [5,6,[8][9][10][11][12][13][14]. Rangelands globally account for 80-85% of feed needs for…”
Section: Introductionmentioning
confidence: 99%